Prevalence and Implications of “Must‐Kill” Angling Regulations for the Management of Invasive Fishes - Kevin A. Adeli; Bryan D. Neff; Steven J. Cooke (Fisheries Management and Ecology, 2026)
Freshwater biodiversity is increasingly threatened by invasive species, which can disrupt native fish populations and the fisheries they support. Must‐kill regulations, which prohibit the live release of invasive fish caught by recreational anglers, are a management strategy that can be implemented to limit the negative effects of invasive fish populations. Our review of angling regulations around the globe revealed that must‐kill regulations for numerous species were frequently enacted in countries including Canada, Japan, and the USA. Suggested benefits of must‐kill regulations included limiting invasive species population size and preventing their dispersal, among others. While these benefits were plausible, we found no rigorous assessments of their effectiveness. Moreover, must‐kill regulations can introduce concerns such as angler opposition and species misidentification. Here, we bolstered sparse evidence with anecdotes and perspectives to identify potential advantages and drawbacks of must‐kill regulations. We also provided guidelines for implementing must‐kill regulations that emphasize strategies to increase the likelihood of success while minimizing unintended consequences. Specific guidelines vary depending on management objectives, but generally include a preliminary feasibility and risk assessment followed by post‐implementation monitoring of efficacy and consequences.

Hide or seek: presence of stream shelter influences the foraging behaviour of juvenile Atlantic salmon (Salmo salar, Linnaeus 1758) - Christian A. Therrien; Yolanda E. Morbey; Bryan D. Neff (Environmental Biology of Fishes, 2022)

Similarity at the major histocompatibility complex class II does not influence mating patterns in bluegill (Lepomis macrochirus) - Lucas Silveira; Shawn R. Garner; Bryan D. Neff (Behavioral Ecology and Sociobiology, 2020)

Relationship between cardiac performance and environment across populations of Atlantic salmon (Salmo salar): a common garden experiment implicates local adaptation - Kayla J. Gradil; Shawn R. Garner; Chris C. Wilson; Anthony P. Farrell; Bryan D. Neff (Evolutionary Ecology, 2016)

Transcriptional profiling of two Atlantic salmon strains: implications for reintroduction into Lake Ontario - Xiaoping He; Chris C. Wilson; Kyle W. Wellband; Aimee Lee S. Houde; Bryan D. Neff; Daniel D. Heath (Conservation Genetics, 2015)

Rapid evolution of sperm length in response to increased temperature in an ectothermic fish - Ross D. Breckels; Bryan D. Neff (Evolutionary Ecology, 2014)

Rapid evolution in response to increased temperature maintains population viability despite genetic erosion in a tropical ectotherm - Ross D. Breckels; Shawn R. Garner; Bryan D. Neff (Evolutionary Ecology, 2014)

High degree of paternity loss in a species with alternative reproductive tactics - Karen M. Cogliati; Bryan D. Neff; Sigal Balshine (Behavioral Ecology and Sociobiology, 2013)

Songbird genetic diversity is lower in anthropogenically versus naturally fragmented landscapes - Elizabeth A. MacDougall-Shackleton; Michael Clinchy; Liana Zanette; Bryan D. Neff (Conservation Genetics, 2011)

MHC-mediated local adaptation in reciprocally translocated Chinook salmon - Melissa L. Evans; Bryan D. Neff; Daniel D. Heath (Conservation Genetics, 2010)

Pollution-induced behavioural effects in the brown bullhead (Ameiurus nebulosus) - Ross D. Breckels; Bryan D. Neff (Ecotoxicology, 2010)

Parasite mediated homogenizing selection at the MHC in guppies - Bonnie A. Fraser; Bryan D. Neff (Genetica, 2010)

Major histocompatibility complex heterozygote advantage and widespread bacterial infections in populations of Chinook salmon ( Oncorhynchus tshawytscha ) - MELISSA L. EVANS; BRYAN D. NEFF (Molecular Ecology, 2009)
Despite growing evidence for parasite‐mediated selection on the vertebrate major histocompatibility complex (MHC), little is known about variation in the bacterial parasite community within and among host populations or its influence on MHC evolution. In this study, we characterize variation in the parasitic bacterial community associated with Chinook salmon ( Oncorhynchus tshawytscha ) fry in five populations in British Columbia (BC), Canada across 2 years, and examine whether bacterial infections are a potential source of selection on the MHC. We found an unprecedented diversity of bacteria infecting fry with a total of 55 unique bacteria identified. Bacterial infection rates varied from 9% to 29% among populations and there was a significant isolation by distance relationship in bacterial community phylogenetic similarity across the populations. Spatial variation in the frequency of infections and in the phylogenetic similarity of bacterial communities may result in differential parasite‐mediated selection at the MHC across populations. Across all populations, we found evidence of a heterozygote advantage at the MHC class II, which may be a source of balancing selection on this locus. Interestingly, a co‐inertia analysis indicated only susceptibility associations between a few of the MHC class I and II alleles and specific bacterial parasites; there was no evidence that any of the alleles provided resistance to the bacteria. Our results reveal a complex bacterial community infecting populations of a fish and underscore the importance of considering the role of multiple pathogens in the evolution of host adaptations.

Inter‐population variation in multiple paternity and reproductive skew in the guppy - BRYAN D. NEFF; TREVOR E. PITCHER; INDAR W. RAMNARINE (Molecular Ecology, 2008)
We use microsatellite loci to detail the multiple paternity patterns in broods from 10 wild populations of the guppy ( Poecilia reticulata ) found in Northern Trinidad. The populations span two major drainages comprising the Caroni and the Oropouche, and include sites that are characterized by either high or low predation. Across the populations the frequency of multiple paternity is high with 95% (range: 70%–100%) of broods having multiple sires. Broods have an average of 3.5 sires (range: 1–9) and a mixed‐model analysis suggests that broods from high predation sites have marginally more sires than do those from low predation sites, but this is true only in the Oropouche drainage. There is no difference in sire number between predation sites in the Caroni drainage. Brood size, but not female body length, is correlated with the number of sires and the correlation cannot be attributed solely to the stochastic process associated with sperm competition and a ‘fair raffle’. Within broods there is significant skew in reproductive success among males, which may reflect variation in sperm competitiveness or female choice. There is, however, no difference in the skew among populations from different predation regimes or drainages. Finally, high predation populations were characterized by increased genetic variability at the microsatellite loci, suggesting a larger effective population size. We discuss explanations for the high degree of multiple paternity but the general lack of any major differences among broods from ecologically different populations.

Multiple paternity and kin recognition mechanisms in a guppy population - TIMOTHY J. A. HAIN; BRYAN D. NEFF (Molecular Ecology, 2007)
Help directed toward kin (nepotism) is an important example of social behaviour. Such helping behaviour requires a mechanism to distinguish kin from nonkin. The prevailing kin recognition hypothesis is that when familiarity is a reliable cue of relatedness, other mechanisms of recognition will not evolve. However, when familiarity is an unreliable cue of relatedness, kin recognition by phenotype matching is instead predicted to evolve. Here we use genetic markers to show that guppies ( Poecilia reticulata ) from a population in a tributary of the Paria River in Trinidad are characterized by a high degree of multiple mating with 95% of broods having more than one sire and some dams having offspring sired by six males. These levels of multiple mating are the highest reported among live‐bearing fishes. The mean relatedness of brood‐mates was 0.36 (as compared to 0.5 for full‐siblings). Therefore, familiarity does not seem to be a reliable mechanism to assess full‐sibling relatedness. Using two‐choice behavioural trials, we found that juveniles from this population use both phenotype matching and familiarity to distinguish kin from nonkin. However, we did not find strong evidence that the guppies use these mechanisms to form shoals of related individuals as adults, which is similar to results from other guppy populations in Trinidad. The use of both familiarity and phenotype matching is discussed in the context of the Paria River guppy population's mating system and ecology. Overall, these data provide support for the kin recognition hypothesis and increase our understanding of the evolution of kin recognition systems.

Genetic quality and offspring performance in Chinook salmon: implications for supportive breeding - Trevor E. Pitcher; Bryan D. Neff (Conservation Genetics, 2007)

MHC class IIB alleles contribute to both additive and nonadditive genetic effects on survival in Chinook salmon - TREVOR E. PITCHER; BRYAN D. NEFF (Molecular Ecology, 2006)
The genes of the major histocompatibility complex (MHC) are found in all vertebrates and are an important component of individual fitness through their role in disease and pathogen resistance. These genes are among the most polymorphic in genomes and the mechanism that maintains the diversity has been actively debated with arguments for natural selection centering on either additive or nonadditive genetic effects. Here, we use a quantitative genetics breeding design to examine the genetic effects of MHC class IIB alleles on offspring survivorship in Chinook salmon ( Oncorhynchus tshawytscha ). We develop a novel genetic algorithm that can be used to assign values to specific alleles or genotypes. We use this genetic algorithm to show simultaneous additive and nonadditive effects of specific MHC class IIB alleles and genotypes on offspring survivorship. The additive effect supports the rare‐allele hypothesis as a potential mechanism for maintaining genetic diversity at the MHC. However, contrary to the overdominance hypothesis, the nonadditive effect led to underdominance at one heterozygous genotype, which could instead reduce variability at the MHC. Our algorithm is an advancement over traditional animal models that only partition variance in fitness to additive and nonadditive genetic effects, but do not allocate these effects to specific alleles and genotypes. Additionally, we found evidence of nonrandom segregation during meiosis in females that promotes an MHC allele that is associated with higher survivorship. Such nonrandom segregation could further reduce variability at the MHC and may explain why Chinook salmon has one of the lowest levels of MHC diversity of all vertebrates.

Genetic quality and sexual selection: an integrated framework for good genes and compatible genes - BRYAN D. NEFF; TREVOR E. PITCHER (Molecular Ecology, 2005)
Why are females so choosy when it comes to mating? This question has puzzled and marveled evolutionary and behavioral ecologists for decades. In mating systems in which males provide direct benefits to the female or her offspring, such as food or shelter, the answer seems straightforward — females should prefer to mate with males that are able to provide more resources. The answer is less clear in other mating systems in which males provide no resources (other than sperm) to females. Theoretical models that account for the evolution of mate choice in such nonresource‐based mating systems require that females obtain a genetic benefit through increased offspring fitness from their choice. Empirical studies of nonresource‐based mating systems that are characterized by strong female choice for males with elaborate sexual traits (like the large tail of peacocks) suggest that additive genetic benefits can explain only a small percentage of the variation in fitness. Other research on genetic benefits has examined nonadditive effects as another source of genetic variation in fitness and a potential benefit to female mate choice. In this paper, we review the sexual selection literature on genetic quality to address five objectives. First, we attempt to provide an integrated framework for discussing genetic quality. We propose that the term ‘good gene’ be used exclusively to refer to additive genetic variation in fitness, ‘compatible gene’ be used to refer to nonadditive genetic variation in fitness, and ‘genetic quality’ be defined as the sum of the two effects. Second, we review empirical approaches used to calculate the effect size of genetic quality and discuss these approaches in the context of measuring benefits from good genes, compatible genes and both types of genes. Third, we discuss biological mechanisms for acquiring and promoting offspring genetic quality and categorize these into three stages during breeding: (i) precopulatory (mate choice); (ii) postcopulatory, prefertilization (sperm utilization); and (iii) postcopulatory, postfertilization (differential investment). Fourth, we present a verbal model of the effect of good genes sexual selection and compatible genes sexual selection on population genetic variation in fitness, and discuss the potential trade‐offs that might exist between mate choice for good genes and mate choice for compatible genes. Fifth, we discuss some future directions for research on genetic quality and sexual selection.

Paternity and condition affect cannibalistic behavior in nest-tending bluegill sunfish - Bryan D. Neff (Behavioral Ecology and Sociobiology, 2003)

Cross-correlation bias in lag analysis of aquatic time series - Julian D. Olden; Bryan D. Neff (Marine Biology, 2001)